2012
DOI: 10.1111/j.1346-8138.2012.01640.x
|View full text |Cite
|
Sign up to set email alerts
|

Prurigo pigmentosa: Clinicopathological study and analysis of 50 cases in Korea

Abstract: Prurigo pigmentosa is a recurrent dermatosis with severe pruritus and several peculiar clinical features. Its exact etiology and pathogenesis are unclear. The aim of this study was to investigate the clinical features and chronological changes in the histopathology of prurigo pigmentosa in Korean patients and to assess the etiology of this condition. We reviewed the medical records, clinical photographs and biopsy specimens from 50 patients diagnosed with prurigo pigmentosa. Mean age at diagnosis was 23.7 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
3
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(87 citation statements)
references
References 32 publications
5
72
3
6
Order By: Relevance
“…10 The distribution of skin lesions was mostly symmetrical and most frequently affected the back, as well as the lumbosacral region, nape, shoulder and chest. 1,6,8 We also report for the first time a case in which the armpit was affected. 6,8,11 This disease can be divided into four chronological stages: early, fully developed, resolving and late.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…10 The distribution of skin lesions was mostly symmetrical and most frequently affected the back, as well as the lumbosacral region, nape, shoulder and chest. 1,6,8 We also report for the first time a case in which the armpit was affected. 6,8,11 This disease can be divided into four chronological stages: early, fully developed, resolving and late.…”
Section: Discussionmentioning
confidence: 84%
“…This disease usually occurs in patients in their late teens and early twenties. Females were predominantly affected by this disease, 1,6 which sometimes erupts in pregnant woman. 10 The distribution of skin lesions was mostly symmetrical and most frequently affected the back, as well as the lumbosacral region, nape, shoulder and chest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies discuss the relation between prurigo pigmentosa and starvation, carbohydrate-poor diets due to their high ketogenic effect, and the ketosis observed in diabetes mellitus (4,(8)(9)(10). In a series of four cases that Hijazi et al presented in 2014, they observed that one patient developed the lesions after dieting during the month of Ramadan, and two patients developed lesions after a strict diet (7).…”
Section: Case Reportmentioning
confidence: 99%